The culture of architecture in Dublin 1940-1965 : a study of architectural discourse, key competitions and buildings of health, home and worship - Rowley, Ellen (Trinity College (Dublin, Ireland). Department of History of Art and Architecture, 2011)
The thesis is a history of architecture in Dublin from c.1940 to c.1965. It is the first in-depth examination of Irish architecture during this period. It explores various relationships around the production and culture of architecture over a twenty-five year period such as patronage (local authority, Catholic Church and semi-state), contemporary architectural discourse, architectural education, international influences, stylistic tendencies, technological development and the flowering of town planning. It is an interpretative history which attempts to sketch a comprehensive picture of architecture in its cultural, social, economic and international contexts, 1940 - 1965.
Keywords: History of Art and Architecture, Ph.D.; Ph.D. Trinity College Dublin